TMCO1, as a potential biomarker of prognosis and immunotherapy response, regulates head and neck squamous cell carcinoma proliferation and migration - Ting Li; Lu Chen; Guangkai Zhou; Yuhan Deng; Meng Zhou; Mingze Yan; Shuyan Dong; Kaixun Xing; Shan Yu; Hongjiang He (Discover Oncology)
Abstract Transmembrane and coiled-coil domains 1 (TMCO1), an endoplasmic reticulum transmembrane protein, actively regulates intracellular Ca2+ concentration and is associated with poor prognosis in several cancers. This study shows that TMCO1 is a potential biological prognostic indicator and therapeutic target for head and neck squamous cell carcinoma (HNSCC) by regulating the proliferation and migration of cancer cells, especially migration. We obtained TMCO1 expression data of HNSCC and normal tissues from The Cancer Genome Atlas (TCGA) and other databases and verified them with immunohistochemical staining. The results showed that high TMCO1 expression was significantly associated with HNSCC survival and tumor progression and was an independent prognostic factor for HNSCC. In addition, nomogram and receiver operating characteristic (ROC) curve, gene ontology, gene concentration and gene network analysis were used to reveal the function and regulatory mechanism of TMCO1. In vitro experiments confirmed that TMCO1 could promote proliferation, migration, invasion, adhesion and clonal formation of HNSCC cells. Furthermore, we analyzed the relationship between TMCO1 and tumor microenvironment, immune infiltration, immunotherapy and drug sensitivity, and found that patients with low TMCO1 expression were more suitable for immunotherapy, and suggested the selection of chemotherapy drugs. In conclusion, TMCO1 is a reliable biomarker in HNSCC, offering valuable guidance for clinical diagnosis and therapeutic strategies. These findings highlight its potential as a target for precision oncology in HNSCC.